From the experience of motivation formation in students of medical universities - Nykolajenko-Kamyshova Тетяна (Psychosomatic Medicine and General Practice, 2019)
There was conducted a questionnaire of 43 students of 5-6 courses of the higher educational establishment to evaluate the motivational levers in the formation of professional status. The issues related to orientation in choosing a doctor’s profession, determining the most important academic subjects in teaching and forming a doctor’s outlook and basic motivations for professional growth, personal assessment of the attitude to one’s health were considered. The majority of respondents (70%) indicated that the medical speciality was chosen under the influence of their parents according to dynasty principles. Learning process used in schools and “homework” process was considered appropriate because it greatly facilitates better understanding of subjects and self-organization. The most important basic subjects for the respondents were anatomy, histology, physiology, pharmacology; because they are the basis for understanding the etiopathogenesis and clinical manifestations of the disease. Simultaneous study of these disciplines provides the basis for the formation of a unified view of the functional and morphological features of the body and the consequences of disorders in the process of disease. A great influence on the interest of students in the study of clinical disciplines is the recognition of the authority of the teacher. Conducting debates, brainstorming sessions, and the presence of students at clinical conferences enables to communicate most actively and express your views on problem situations. More than 20% of students wanted to gain experience in research. Concerning the formation of clinical thinking, the most necessary was considered to be clinical examinations with the demonstration of patients with the analysis of the medical history and the subsequent prognostic assessment of the course of the pathological process. The most interested in conducting clinical trials were trainees who worked part-time in health care facilities and involved in doctor-patient interactions. Emergencies and the need to assist patients during the duty cycle required concentration and proper accountability. In the formation of motivational principles of professional development and success the following ones were considered important: the process of employment - 72.1%, the social value of the profession - 54.9%, career opportunities - 41.7%, independence in decision-making - 25.4%. Staying in an inpatient atmosphere, supervising patients and exposing the negative direct impact of bad habits on the course of the disease require careful assessment and a personal focus on keeping to a healthy lifestyle. The physician should be an authority for the patient and a role model.